PROTOTYPE RANCANG BANGUN SISTEM LAMPU DAN KIPAS OTOMATIS MENGGUNAKAN SENSOR PIR GERAK SUHU DAN CAHAYA BERBASIS ARDUINO UNO - Teguh Setiadi; Laksaman Haidar; Muhamad Fadlan (LPPM Universitas Widya Dharma, 2022)
Along with the development of science and technology, many ideas in the field of digital electronics have emerged. Developed digital systems are applied to microcontroller technology, this system simplifies from conventional to automated systems. This thesis is intended to examine the use of a lighting control microcontroller. In general, the lights in the house are still regulated by a switch, so users turn on and off manually. The observation method, interview method, documentation media and literature study method. The automatic working function of smart lights uses light intensity and distance sensors, namely, turning on the lights according to the detection of light intensity in the room and human presence using motion sensors. The conclusion that can be drawn from the assembly and manufacture of smart lamps is that light and distance sensors can detect room light and the presence of humans in it, if the light sensor detects the intensity of light above a predetermined limit and there is no human presence in it, the lamp will not turn on. Vice versa, if the light sensor detects light above a predetermined limit and human presence is detected in it, the light will turn on. The light will stop or turn off automatically when the light intensity is below or equal to a predetermined limit